Intercommunal warfare and ethnic peacemaking : the dynamics of urban violence in Central Asia - Kutmanaliev, Joldon (McGill-Queen's studies in protest, power, and resistance, 2023)
"With increasing urban population density, conflicts in cities erupt more frequently and violently. Cities have become hotspots for armed combat, highlighting the urgency of understanding the impact of local communities and urban factors on the development of violent conflict. Joldon Kutmanaliev presents a novel approach to analyzing communal violence and armed conflicts in urban zones. Drawing from fieldwork in cities of southern Kyrgyzstan, he explains local-level variations in violence across neighbourhoods during the most intense and violent episode of urban communal violence in Central Asia--the clashes between Kyrgyz and Uzbeks in June 2010. Kutmanaliev explains why armed violence affects some urban neighbourhoods but not others, why local communities react differently to the same existential threat, how they deal with a deteriorating security environment and interethnic fears, and how different types of urban planning and urban landscapes influence the spread of violence. Importantly, the book identifies key factors that help local communities and their leaders to negotiate non-aggression pacts and control local constituencies, and therefore successfully prevent violence. Intercommunal Warfare and Ethnic Peacemaking explains communal war and ethnic peacemaking on the level of neighbourhood communities--a perspective that is largely absent in previous studies."--